Adverse reactions to immunotherapy are associated with different patterns of sensitization to grass allergens. Issue 5 (13th February 2015) - Sastre, J.; Rodríguez, F.; Campo, P.; Laffond, E.; Marín, A.; Alonso, M. D.
Abstract The aim of the study was to investigate whether adverse drug reactions (ADRs) during immunotherapy with a grass extract (AVANZ® Phleum, ALK‐Abelló) are related to the different patterns of sensitization of patients to grass allergens. A total of 192 patients with rhinitis and/or asthma sensitized to grass pollen received a 4‐week updosing with five injections. ADRs were evaluated following EAACI guidelines. A total of 432 ADRs in 133 (69%) patients were recorded, 64% local and 31% systemic. There was a significant association between the number of grass allergens that sensitized the patients and the total number of ADRs (P = 0.004) occurred locally (P = 0.003) and systemically (P = 0.01). Sensitization to Phl p1 + Phl p5 or Phl p1 + Phl p5 + Phl p12 was significantly associated with a higher frequency of local or systemic reactions (P = 0.001, both). Different patterns of sensitization to grass allergens may potentially be considered a risk marker to the development of ADRs to immunotherapy.